High-Throughput Customization of Plant Microbiomes for Sustainable Agriculture - Du, Jianfeng; Li, Yang; Yin, Ziyi; Wang, Hongfeng; Zhang, Xiaoying; Ding, Xinhua (Frontiers in Plant Science, 2020)
Soil microorganisms can form a stable dynamic system with plant root systems. The composition of soil microorganisms is related to the growth and stress resistance of plants; in turn, soil microorganisms are also regulated by plant genotypes and root exudates. Therefore, research on how to identify microorganisms that are beneficial or harmful to plants, study the interaction between microorganisms and plants, and form stable microbial communities for better plant growth plays an important role in sustainable precision agriculture. It is of great significance to identify and analyze rhizosphere microorganisms and plant endophytes through high-throughput methods, especially to analyze which microorganisms are beneficial to plants, which are harmful to plants, and which are opportunistic pathogens. This review provides a theoretical basis and outlook for the utilization of beneficial microbes in sustainable precision agriculture.